Parental wellbeing, parenting, and child mental health in families with young children in Arghakhanchi, Nepal - Sirjana Adhikari; Hari Rana³; Mahesh Prasad Joshi; Sabrina Cheng; Theresa Castillo; Keng-Yen Huang (BMC Pediatrics)
Abstract Background Children’s social-emotional development and mental well-being are critical to adult mental health. However, little is known about the mechanisms or factors that contribute to poor child mental health in low- and middle-income countries. Given the lack of child mental health research to guide interventions or social-emotional learning programs and policy planning, the present study aimed to address these knowledge gaps by examining the psychopathology mechanism involved in the development of childhood mental health problems. Methods This cross-sectional study recruited parents (N = 393) whose children attended preschool to primary classes in the Arghakhanchi district of Nepal. Data were gathered through parent interviews. Structural Equation Modeling was used to examine the pathways of the mediational mechanism that examined the influence of parental well-being on parenting and children’s mental health outcomes. Results Approximately 22% of the parents were at risk for moderate to severe mental health problems (anxiety: 24%, depression:19%). Parental mental health problems were higher in families who reported food insecurity, among female parents, less educated parents, and those who perceived themselves on a lower social ladder. Parental mental health, social support, and perceived class were associated with parent-child conflict. Greater parent-child conflict was associated with decreased social competence and increased anger, anxiety, and depression in children. Conclusion The results partially support the mediational model that Nepali parents’ well-being (especially in mental health symptoms, social support, and perception of family’s social class domains) is associated with less optimal parenting and, in turn, greater child mental health problems and lower social competence. This study provides new evidence of cross-cultural consistency in child psychopathology and guides the development of evidence-based programs to prevent and promote mental health among Nepali children and families.